2008
DOI: 10.1111/j.1523-536x.2008.00243.x
|View full text |Cite
|
Sign up to set email alerts
|

How Do Physicians and Midwives Manage the Third Stage of Labor?

Abstract: A major difference was found between physicians and midwives in the management of third-stage labor. Physicians routinely implemented active management of the third stage of labor; midwives preferred expectant approaches, principally based on women's preference. Provincial data did not show differences in postpartum hemorrhage or transfusion rates by practitioner type.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
71
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(74 citation statements)
references
References 18 publications
2
71
1
Order By: Relevance
“…Our survey suggests this policy is followed for vaginal births conducted by obstetricians, but midwives were more likely to give the uterotonic later. Similar practice for obstetricians and midwives has been reported elsewhere [14]. This may be because if the midwife is alone she will not be able to give the uterotonic drug until after the baby is born, whilst obstetricians are less likely to attend a delivery alone.…”
Section: Discussionmentioning
confidence: 53%
“…Our survey suggests this policy is followed for vaginal births conducted by obstetricians, but midwives were more likely to give the uterotonic later. Similar practice for obstetricians and midwives has been reported elsewhere [14]. This may be because if the midwife is alone she will not be able to give the uterotonic drug until after the baby is born, whilst obstetricians are less likely to attend a delivery alone.…”
Section: Discussionmentioning
confidence: 53%
“…22 Although active management is practised in both high-and low-income countries, the relative timing of each component varies. [23][24][25] In Sweden it is recommended that all women giving birth vaginally be given an intravenous injection of 10 iu of oxytocin as soon as the baby is born. 26 However, the entire AMTSL procedure has not been adopted, and has been questioned by care providers.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, a number of maternal circumstances warrant ICC to the benefit of the mother-infant dyad, including placental previa, placental abruption, and velamentous cord insertion [2,3]. While a recent Cochrane review showed that DCC does not increase the risk of postpartum hemorrhage in more mature infants [44], this concern continues to be one of the primary reasons obstetricians cite for performing ICC [12,22].…”
Section: Reasons To Perform Iccmentioning
confidence: 99%
“…The practice of increasing placental-fetal transfusion at birth was considered standard of care until the 1960 s when practice shifted to immediate clamping of the cord and handing off the infant to the pediatric team for resuscitation and as active management of the third stage of labor [2,3]. At that time, increased placental-fetal transfusion was associated with hyperbilirubinemia and polycythemia, with additional evidence that delays in resuscitation may worsen neonatal outcomes [4][5][6].…”
Section: Introduction and Historical Perspectivementioning
confidence: 99%